Entrepreneurship Development: A Study of Government Initiatives in Rupandehi - Thapa, Kiran (Kalika Journal of Multidisciplinary Research, 2025)
Entrepreneurship is a key driver of economic growth, employment creation, and poverty reduction. The Government of Nepal has introduced policies, financial schemes, training programs, infrastructure development, and market promotion to support it. This study evaluates the status and effectiveness of these initiatives in fostering entrepreneurship development in Rupandehi district. Guided by a positivist philosophy with a deductive approach, a cross-sectional time frame, and a descriptive research design, the study assessed 17,823 registered cottage and small entrepreneurs, from which 410 valid responses were obtained through convenience sampling. Data were collected using a structured questionnaire measuring five dimensions of government support, and reliability was confirmed through a pilot test. Analysis employed descriptive statistics, reliability and validity tests, and PLS-SEM. Results reveal that policies, legal frameworks, and business infrastructure have significant positive effects on entrepreneurship development. Contrary to this, financial support, education and skill development, and market access and promotional programs show weaker and insignificant influence. These findings highlight that clarity in regulatory provisions and infrastructure facilities remains an effective driver of entrepreneurship. At the same time other initiatives require substantial improvement in design and implementation. Strengthening financial access, ensuring continuity and relevance of training programs, and expanding promotional efforts are necessary to enhance inclusiveness and sustainability of entrepreneurship growth in Rupandehi. The study provides empirical evidence on the effectiveness of government initiatives in a local context. Further, the study offers insights for policymakers to refine existing programs and design the initiatives that better align with the needs of entrepreneurs in Rupandehi, Nepal.